Enhanced mosquitocidal efficacy of pyrethroid insecticides by nanometric emulsion preparation towards Culex pipiens larvae with biochemical and molecular docking studies - Nehad E. M. Taktak; Mohamed E. I. Badawy; Osama M. Awad; Nadia E. Abou El-Ela; Salwa M. Abdallah (SpringerOpen, 2021)
Abstract Background The growing threat of vector-borne diseases and environmental pollution with conventional pesticides has led to the search for nanotechnology applications to prepare alternative products. Methods In the current study, four pyrethroid insecticides include alpha-cypermethrin, deltamethrin, lambda-cyhalothrin, and permethrin were incorporated into stable nanoemulsions. The optimization of nanoemulsions is designed based on the active ingredient, solvent, surfactant, sonication time, sonication cycle, and sonication energy by factorial analysis. The nanoscale emulsions' droplet size and morphology were measured by dynamic light scattering (DLS) and transmission electron microscopy (TEM), respectively. The toxicity of nanoemulsions against Culex pipiens larvae was evaluated and compared with the technical and commercial formulations. The in vitro assay of adenosine triphosphatase (ATPase), carboxylesterase (CaE), and glutathione-S-transferase (GST) were also investigated. Furthermore, molecular docking was examined to assess the binding interactions between the tested pyrethroids and the target enzymes. Also, an ecotoxicological assessment of potential effects of the tested products on the freshwater alga Raphidocelis subcapitata was determined according to OECD and EPA methods. The emulsifible concentration (EC50) and NOEC (no observed effect concentration) values were estimated for each insecticide and graded according to the GHS to determine the risk profile in aquatic life. Results The mean droplet diameter and zeta potential of the prepared pyrethroid nanoemulsions were found to be in the range of 72.00-172.00 nm and − 0.539 to − 15.40 mV, respectively. All insecticides' nanoemulsions showed significantly high toxicity (1.5-2-fold) against C. pipiens larvae compared to the technical and EC. The biochemical activity data proved that all products significantly inhibited ATPase. However, GST and CaE were significantly activated. Docking results proved that the pyrethroids exhibited a higher binding affinity with CaE and GST than ATPase. The docking scores ranged from − 4.33 to − 10.01 kcal/mol. Further, the biosafety studies of the nanopesticides in comparison with the active ingredient and commercial EC were carried out against the freshwater alga R. subcapitata and the mosquitocidal concentration of nanopesticides was found to be non-toxic. Conclusion The mosquitocidal efficacy of nano-pyrethroids formulated in a greener approach could become an alternative to using conventional pesticide application in an environmentally friendly manner.